PENERAPAN KONSELING INDIVIDU DENGAN PENDEKATAN CLIENT CENTERED TERHADAP PENGENDALIAN EMOSI PADA LANSIA DI PANTI SOSIAL LANJUT USIA HARAPAN KITA PALEMBANG - Eges Progito; Suryati Suryati; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This thesis is entitled "Application of Individual Counseling with a Client Centered Approach to Controlling the Emotions of the Elderly at the Harapan Kita Palembang Elderly Social Home". The background of this research is a client who experiences unstable emotions which is reflected in his often impulsive behavior. The aim of this research is to describe the emotional control of the elderly, and to determine the application of individual counseling with a client-centered approach to controlling the emotions of the elderly at the Harapan Kita Palembang elderly social institution. This type of research is a case study with qualitative methods. The subjects of this research were client "A" and employees at the Harapan Kita Palembang elderly social home. Data collection techniques in this research are observation, interviews and documentation. The data analysis technique uses data analysis techniques from Miles and Huberman, namely there are three types of activities, namely data reduction, data display and verification. The results of this research show that before individual counseling was given to client "A" there was quite a high level characterized by his emotions being uncontrollable, often feeling uncomfortable, and liking to compare himself with other people and after being given individual counseling client "A" slowly experienced a decline in his emotions. . The application of individual counseling with a client centered approach uses three stages, namely the initial stage of counseling, the middle stage (work stage), the final stage of counseling (action stage), so that the results obtained are that client "A" has experienced many changes, where client "A" can finding meaning and controlling emotions, not denying and running away from emotions, not exaggerating emotions, utilizing emotions as unlimited power, and using emotions proportionally.